On the rooftop : a novel - Sexton, Margaret Wilkerson (Ecco, an imprint of HarperCollinsPublishers, 2022)
"A stunning novel about a mother whose dream of musical stardom for her three daughters collides with the daughters' ambitions for their own lives--set against the backdrop of gentrifying 1950s San Francisco"--